Src-Mediated Cross-Talk between Farnesoid X and Epidermal Growth Factor Receptors Inhibits Human Intestinal Cell Proliferation and Tumorigenesis - Peng, Zhongsheng (Public Library of Science, 2012)
Besides its essential role in controlling bile acid and lipid metabolism, the farnesoid X receptor (FXR) protects against intestinal tumorigenesis by promoting apoptosis and inhibiting cell proliferation. However, the mechanisms underlying these anti-proliferative actions of FXR remain to be elucidated. In the present study, we examined the effects of FXR activation (FXR overexpression and treatment with an FXR agonist GW4064) and inactivation (treatment with FXR siRNA and an FXR antagonist guggulsterone) on colon cancer cell proliferation in vitro using human colon cancer cell lines (H508, SNU-C4 and HT-29) and in vivo using xenografts in nude mice. Blocking FXR activity with guggulsterone stimulated time- and dose-dependent EGFR (Tyr845) phosphorylation and ERK activation. In contrast, FXR overexpression and activation with GW4064 attenuated cell proliferation by down-regulating EGFR (Tyr845) phosphorylation and ERK activation. Treatment with guggulsterone and GW4064 also caused dose-dependent changes in Src (Tyr416) phosphorylation. In stably-transfected human colon cancer cells, overexpression of FXR reduced EGFR, ERK, Src phosphorylation and cell proliferation, and in nude mice attenuated the growth of human colon cancer xenografts (64% reduction in tumor volume; 47% reduction in tumor weight; both P<0.01). Moreover, guggulsterone-induced EGFR and ERK phosphorylation and cell proliferation were abolished by inhibiting activation of Src, EGFR and MEK. Collectively these data support the novel conclusion that in human colon cancer cells Src-mediated cross-talk between FXR and EGFR modulates ERK phosphorylation, thereby regulating intestinal cell proliferation and tumorigenesis.